SOME ASPECTS OF THE HISTORY OF OPIATES IN THE CONTEXT OF NOWADAYS DRUG ADDICTION PROBLEMS - Logash, M.; Pokotylo, P. (World of Medicine and Biology, 2013)
The overview of the opiae's history and the relationship between historical mistake, made by humanity with opiates, and nowadays problems with drug addiction, has made in this article. It becomes clear that keys problems, which society has today with drug addiction, was made by humanity himself during different historical periods, and main reasons were the disregard and disrespectful to drug addictions problem, and using the opiates without sufficient researching of their action and possible complications, as well as huge political, economic and social influence on purely medical and scientific problems.
Keywords: opiates; opioids; drug addiction; history of opiates; maintenance treatment